Using modified Fenn diagrams to assess ventilatory acclimatization during ascent to high altitude: Effect of acetazolamide - Rodion Isakovich; Valerie C. Cates; Brandon A. Pentz; Jordan D. Bird; Emily R. Vanden Berg; Emily M. deFreitas; Cassandra E. Nysten; Jack K. Leacy; Ken D. O'Halloran; Thomas D. Brutsaert; Mingma T. Sherpa; Trevor A. Day (Experimental Physiology, 2024)
Abstract High altitude (HA) ascent imposes systemic hypoxia and associated risk of acute mountain sickness. Acute hypoxia elicits a hypoxic ventilatory response (HVR), which is augmented with chronic HA exposure (i.e., ventilatory acclimatization; VA). However, laboratory‐based HVR tests lack portability and feasibility in field studies. As an alternative, we aimed to characterize area under the curve (AUC) calculations on Fenn diagrams, modified by plotting portable measurements of end‐tidal carbon dioxide (PETCO2) against peripheral oxygen saturation (SpO2) to characterize and quantify VA during incremental ascent to HA (n = 46). Secondarily, these participants were compared with a separate group following the identical ascent profile whilst self‐administering a prophylactic oral dose of acetazolamide (Az; 125 mg BID; n = 20) during ascent. First, morning PETCO2 and SpO2 measurements were collected on 46 acetazolamide‐free (NAz) lowland participants during an incremental ascent over 10 days to 5160 m in the Nepal Himalaya. AUC was calculated from individually constructed Fenn diagrams, with a trichotomized split on ranked values characterizing the smallest, medium, and largest magnitudes of AUC, representing high (n = 15), moderate (n = 16), and low (n = 15) degrees of acclimatization. After characterizing the range of response magnitudes, we further demonstrated that AUC magnitudes were significantly smaller in the Az group compared to the NAz group (P = 0.0021), suggesting improved VA. These results suggest that calculating AUC on modified Fenn diagrams has utility in assessing VA in large groups of trekkers during incremental ascent to HA, due to the associated portability and congruency with known physiology, although this novel analytical method requires further validation in controlled experiments. Highlights What is the central question of this study? What are the characteristics of a novel methodological approach to assess ventilatory acclimatization (VA) with incremental ascent to high altitude (HA)? What is the main finding and its importance? Area under the curve (AUC) magnitudes calculated from modified Fenn diagrams were significantly smaller in trekkers taking an oral prophylactic dose of acetazolamide compared to an acetazolamide‐free group, suggesting improved VA. During incremental HA ascent, quantifying AUC using modified Fenn diagrams is feasible to assess VA in large groups of trekkers with ascent, although this novel analytical method requires further validation in controlled experiments.